XIV. studentská vědecká konference Katedry českého jazyka a literatury 17. března 2022 - Procházková, Zuzana (Sborník prací Pedagogické fakulty Masarykovy univerzity, 2022)
Title in English: The XIVth Student Academic Conference of the Department of Czech Language and Literature: 17th March 2022 Proceeding of the conference held on 17th March 2022. The publication contains studies by Zuzana Procházková ("Comparation of Word Formation in the Older and Younger Generation in Selected Villages of the East Moravian Dialect"), Ivana Večeřová ("Specifics of Contemporary Private Electronic Communication"), Radim Ošmera ("Lecturers' Approach to Czech Realities in Teaching Students with Different Mother Tongues"), Tereza Holzerová ("Non-violent Communication in a Czech Language Lesson"), Miroslav Jindra ("Selected Aspects of a Literary Work and their Reception by a Child Reader: Results of Children's Reading Research in the Form of Group Discussion"), Magdaléna Lípová ("Psychosocial Tasks in Early Adolescence in Selected Prose for Children and Youth"), Klára Březinová ("A Theme of Virgin Mary in Selected Works by Jakub Deml"), Tereza Pořízková ("Identity and its Forms in the Book Doupě"), Ondřej Zabloudil Pechník ("The Image of the Rainforest in Czech Prose after 2000") and Tereza Švandová ("French Avant-garde Artistic Movements Originated from Lettrism").